Development of Strategic Interaction of Agents of Entrepreneurship Infrastructure. / Desarrollo de interacción estratégica de agentes de infraestructura de emprendimiento. - PALYAKIN, R.B; SHARAFUTDINOVA, N.S.; SAYDASHEVАV.A.; KHAMETOVA, N.G. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In today’s economic environment, a transformation of relationships of key market participants occurs. It includes entrepreneurs, investors, government structures and infrastructure agents. The subject study includes the main achievements and conclusions of neo-institutionalism theory, the theory of social justice, as well as methodological tools of mathematical modelling and statements of game theory. The article generates a new theoretical and methodological approach to the development of entrepreneurship infrastructure and interaction of its agents. The ways of institutionalizing the cooperation of infrastructural support agents to achieve the best efficiency of entrepreneurship infrastructure are identified. RESUMEN En el entorno económico actual, se produce una transformación de las relaciones de los participantes clave del mercado. Esta incluye a empresarios, inversores, estructuras gubernamentales y agentes de infraestructura. El tema de estudio contiene los principales logros y conclusiones de la teoría del neoinstitucionalismo, teoría de la justicia social, así como herramientas metodológicas de modelado matemático y enunciados de teoría de juegos. El artículo genera un nuevo enfoque teórico y metodológico para el desarrollo de la infraestructura del emprendimiento y la interacción de sus agentes. Se identifican las formas de institucionalizar la cooperación de los agentes de apoyo infraestructural para lograr la mejor eficiencia de la bases del emprendimiento.